‘Je n’ai rien à dire. Seulement à montrer’ : le travail photographique et poétique de Natalie Czech - Vanessa Desclaux (Sillages Critiques)
This text introduces the work of German artist Natalie Czech, whose visual practice stages a meeting point between photography and poetry. For several years Czech has invited spectators to share her affection for the poetic texts that she appropriates. Departing from these poems she invents visual devices through which she can produce new texts and new images in the context of her photographic work. Vanessa Desclaux considers in this text the artist’s methodology and its deployment through various series of works such as Hidden Poems, A Small Bouquet, and Il Pleut. This text looks at the singular relationships that the artist reveals and stages between the fields of the visual arts and of poetry in modern and contemporary times. The author also specifies Czech’s original use of the photographic medium in the production of this recent corpus of works (2010-2012).